DEVELOPING THE VISUAL ABILITY AND CREATIVITY OF PRESCHOOL CHILDREN - Mirzaolimova Kumush; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Pre-school education is the development of children’s abilities and creative abilities through visual activities in educational institutions.